2019
DOI: 10.1200/jco.2019.37.15_suppl.e13506
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant miRNA expression in glioma.

Abstract: e13506 Background: Gliomas are the most common type of primary brain tumors, with a high level of recurrence and mortality. The purpose of the study was to determine the expression profile of micro-RNA targeting components of the Hedgehog, Notch, Wnt, EGFR, TGFβ, HIF1α signaling pathways according to MirTarBase, miRDB, TargetScan. Methods: The study included 30 patients (15 women and 15 men) aged 27 to 76 years with histologically verified glial brain tumors. The RT2-qPCR method in operational biopsy specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The exchange of miRNAs through gap junctions has been reported between glioma cells and from mesenchymal stem cells to glioma cells. It extensively participates in physiopathological process like tissue differentiation, neural development, synaptic formation, and cell apoptosis [ 7 ]. Current studies have shown that miRNA is tightly associated with the onset and developmental process of glioma.…”
Section: Introductionmentioning
confidence: 99%
“…The exchange of miRNAs through gap junctions has been reported between glioma cells and from mesenchymal stem cells to glioma cells. It extensively participates in physiopathological process like tissue differentiation, neural development, synaptic formation, and cell apoptosis [ 7 ]. Current studies have shown that miRNA is tightly associated with the onset and developmental process of glioma.…”
Section: Introductionmentioning
confidence: 99%